Comparison of the Acute Effects of Two Neoprene Knee Sleeves on Balance and Pain in Knee Osteoarthritis: A Randomized, Single-Blinded, Prospective Study - Burcu Ayık,; Nurcan Kağan,; Fulya Bakılan,; Onur Armağan,; Cengiz Bal, (Archives of Rheumatology, 2025)
Background/Aims: Compare the acute effects of two elastic neoprene knee sleeves (one with 4 metal supports) on balance and pain in knee osteoarthritis (KOA). Materials and Methods: Sixty KOA patients (50 F, 10 M; mean age = 61.13 ± 8.6 years) randomized to group 1 (neoprene) or group 2 (neoprene + metal). Outcomes: BBS, TUG, Functional Reach, Fall Index (posturography), and VAS. Assessments before and after wearing sleeves. Sample size via power analysis (α = 0.05, power = 0.99). Results: Both groups improved significantly pre-post (P < .05). Group 2 showed greater BBS improvement, approaching significance (P = .056). Conclusion: Both sleeves provide immediate balance and pain benefits. Sleeve with metal supports yielded slightly greater balance gains; further long-term studies needed.